TOLERANSI ANTAR UMAT BERAGAMA DALAM PERSPEKTIF ISLAM - Aulia, Guruh Ryan (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract; Indonesia is know as a country that has a diversity of ethicities, cultures, races and religions. Every religion has differences that can laed to conflict between religious communities. Saw it is necessary to apply the attitude of tolerance in society. The teachings of tolerance are related to Islam. Islam also gives freedom to anyone to embrace the religion the adhere to. Islam is also a pioneer of tolerance in creating peace and harmony in religious life. The purpose of this study is to describe the Islamic perspective on interfaith tolerance from a theoretical perspective. This research is expected to be a source of knowledge. The type of research used is in the from of library reasearch which is arranged systematically. The results of this study are the basics of tolerance in Islam, the principles of religious tolerance and the limits of tolerance among religious communities. Keywords; Tolerance, Inter-religious and Islam